Optical trapping forces of focused circular partially coherent beams on Rayleigh particles - Yu, Chaoqun; Chen, Fuchang; Zeng, Jun; Huang, Cheng; He, Zhimin; Lin, Huichuan; Zhang, Yongtao; Chen, Ziyang; Pu, Jixiong (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
The optical trapping forces of tightly-focused radially polarized circular partially coherent beams on Rayleigh particles are theoretically investigated. Numerical calculations are performed to study the optical trapping forces on Rayleigh particles for different initial coherent length of the incident circular partially coherent beams. The results show that the magnitude of the gradient force decreases with the reduction of the initial coherent length of the focused radially polarized circular partially coherent beams, while the balanced position (i.e., the position where the optical trapping forces becomes zero) stays constant. Moreover, the focused spot gradually elongates along the optical axis with the reduction of the initial coherent length, and the axial gradient force on Rayleigh particles also decreases gradually with the reduction of the intensity gradient in axial direction. As there exists an spherical aberrant in the focusing optical system, the focal spot in the direction of the optical axis becomes trumpet-shaped, and the optical trapping forces on Rayleigh particles change as well.
Optica Applicata, Vol. 52, 2022, nr 4, s. 575-583
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; tight focusing; radially polarized; circular partially coherent; spherical aberration; optical trapping force